Prediction and Characterization of miRNA/Target Pairs in Non‐Model Plants Using RNA‐seq. Issue 2 (13th May 2019) - Neller, Kira C. M.; Klenov, Alexander; Hudak, Katalin A.
Abstract: Plant microRNAs (miRNAs) are ∼20‐ to 24‐nucleotide small RNAs that post‐transcriptionally regulate gene expression of mRNA targets. Here, we present a workflow to characterize the miRNA transcriptome of a non‐model plant, focusing on miRNAs and targets that are differentially expressed under one experimental treatment. We cover RNA‐seq experimental design to create paired small RNA and mRNA libraries and perform quality control of raw data, de novo mRNA transcriptome assembly and annotation, miRNA prediction, differential expression, target identification, and functional enrichment analysis. Additionally, we include validation of differential expression and miRNA‐induced target cleavage using qRT‐PCR and modified RNA ligase–mediated 5′ rapid amplification of cDNA ends, respectively. Our procedure relies on freely available software and web resources. It is intended for users that lack programming skills but can navigate a command‐line interface. To enable an understanding of formatting requirements and anticipated results, we provide sample RNA‐seq data and key input/output files for each stage. © 2019 The Authors. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.